DESIGN AND DEVELOPMENT OF SPRING PRODUCTION SCHEDULING APPLICATION ON CV DWI TEKNIK - Bobby Hans Pratama; Henry Bambang Setyawan; M.J Dewiyani Sunato (Jurnal Sistem Informasi Universitas Dinamika, 2022)
CV Dwi Teknik is a spring manufacturer located on Balong Dinding street Gg 3, Menganti, Gresik. One of section in CV Dwi Teknik is the production section. In the production section there is booking record that are at once as a production schedule that is carried out in sequence in accordance with the arrival of orders, thus allowing delays on other orders that have a relatively short time limit. From these problems, the production scheduling application is made using priority rules in which there are several methods that will be evaluated with weight on each parameter so that the application can give a decision on which priority rules are best. From the selection of priority rules, the application will print a production order report and production schedule report. The results of the trial conducted with the Head of Production and some Production Staff, the application can sort the order to be produced using the best method that is the result of evaluation based on parameter weighting and the application can also produce calculations of priority rule methods, can print production order reports and production schedule reports.